Pharmacists Knowledge, Attitudes, and Practices Regarding Probiotics and Prebiotics: A Cross-Sectional Study from Palestine - Dala N. Daraghmeh; Leen Kahla; Noor Taqatq (PLoS ONE, 2026)
Background Probiotics and prebiotics are increasingly used globally as part of complementary health intervention for various disorders. Pharmacists, as accessible healthcare providers, are key in guiding safe and effective use. However, little is known about Palestinian pharmacists’ knowledge, attitudes, and practices (KAP) towards these products. This study aimed to assess pharmacists’ KAP regarding probiotics and prebiotics in Palestine and to identify demographic and professional factors associated with pharmacists’ knowledge score. Methods A cross-sectional study was conducted among 400 pharmacists using a self-administered structured questionnaire, covering socio-demographics, probiotics and prebiotics knowledge, attitudes, and practices. Knowledge was assessed using a scoring system, and participants were categorized as having poor (≤50%; 0–17 points), moderate (>50%– < 70%; 18–23 points), or high (≥70%; 24–34 points) knowledge. Descriptive statistics, chi-square tests and multivariable linear regression were used for analysis. All analyses were performed using SPSS version 26. Result Among 400 participating pharmacists, the majority of participants were female (66.25%), aged between 20 and 29 (74.25%), were staff pharmacists (82.50%), and worked in community pharmacies settings (92.25%). The mean knowledge score was 21.3 ± 6.1 (range: 4–34). Most participants demonstrated moderate knowledge (57.8%), while 32.0% achieved high knowledge and 10.3% had poor knowledge. In multivariable analysis, selected factors showed modest associations with knowledge score, including age, probiotic/prebiotic education, and prescription volume (P < 0.05). Attitudes were generally positive, with 85.5% believed they provide health benefits and 81% were willing to recommend them. Practice findings indicated variable self-reported counseling and recommendation behaviors, with barriers related to evidence access and confidence in clinical application. Conclusion Pharmacists in Palestine showed moderate overall knowledge, with positive attitudes towards probiotics and prebiotics, yet knowledge gaps persist. These findings suggest a need for targeted practice-oriented education and continuing professional development to strengthen evidence-based counseling and appropriate clinical application.